The reformist elite and their position on the issue of compulsory conscription 1912 - benhamouda, Murad (The Algerian Historical Journal, 2026)
The beginning of the twentieth century witnessed sharp discussions on the issue of forced conscription of Algerians into the ranks of the French army, which culminated in the last decree issued on February 3, 1912. And it caused a lot of controversy in political circles, as it witnessed the emergence of several parties that expressed their opinion regarding the recruitment issue Whether it is Algerian or French, and among these groups that expressed their position, we find the reformist elite whose position is characterized by disparity and instability, as we find that it was also divided into two parties, a group that agreed to the idea of ​​forced conscription in exchange for France granting privileges to the Algerians, and another party refused forced conscription.